The digital renaissance : classic painting techniques in Photoshop and Painter - Beccia, Carlyn (New York ; London : Focal Press, 2014)
"The Digital Renaissance teaches you how to translate the methods and skills found in traditional art to the digital medium. By covering fundamental painting principles and the basics of digital software, before moving into tutorials that break down key techniques, professional artist Carlyn Beccia teaches you how to use the tools at hand to paint your own works of art. Each chapter showcases one great painter and analyzes the techniques that set each one apart. These techniques are then imitated in step-by-step tutorials, allowing you to achieve amazingly convincing results and bring your own work to new creative heights."--back cover.
Originally published: Lewes: Ilex.
Includes index.
Keywords: Computer art; Computer art -- Technique; Computer graphics; Computer drawing; Adobe Photoshop; Corel Painter; Three-dimensional display systems